Kurangnya Ketepatan Nilai-Nilai Multikultural Dalam Buku Pendidikan Agama Islam dan Budi Pakerti - Sudirman, Megi; Gawdy, Ahmad; Mutamainnatul, Safrotul (JOEAI (Journal of Education and Instruction), 2022)
This study aims to describe an accuracy in the development of multicultural values ​​contained in the book developed by the Ministry of Education and Culture, namely the book on Islamic Religious Education and Budi Pekerti for grade VII SMP. The research method used is the Deductive Method and the Inductive Method. The results of the study show that the content of multicultural values ​​developed in the textbook of Islamic Religious Education and Morals for grade VII, includes 4 values, namely the value of tolerance, the value of democracy, the value of equality, and the value of justice, from the 13 topics of material published. Overall multicultural values ​​account for 36%. The content of multicultural values ​​in textbooks with 13 chapters of discussion topics is considered inaccurate because the percentage is only 36%. In conclusion, the results of the study show that the content of multicultural values ​​developed in the PAI and Budi Pekerti textbooks for class VII SMP includes 4 values, namely the value of tolerance, the value of democracy, the value of equality/equality and the value of justice. The accuracy in developing multicultural values ​​in the textbook component is said to be less precise for multicultural values, overall only reaching 36%, while the measurement scale of 36% falls into the less precise category. Keywords: PAI Textbooks, Character, Accuracy of Components, Multicultural Values